Perlindungan Hukum Bagi Penduduk Sipil Di Wilayah Konflik Armenia Azerbaijan - Cherry Evans Dgwait Timisela; Lucia Charlota Octovina Tahamata; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The protection of the civilian population in the presence of an international armed conflict has been speciafically regulated in Genewa Convention IV 1949 concerning the Protection of Civilians in Conflict Areas. However, in the conflict over the territory of Nagorno-Karabakh by the State of Armenia and Azerbaijan, there are still a number of violations against civilians, where during the conflict, many civilian casualties continue to fall.Purposes of the Research: For this reason, this study aims to examine and determine the mechanisms and forms of protection for civilians in armed conflict according to Genewa Convention IV 1949. Methods of the Research: This research is a normative legal research, using a law approach and a case approach. Research data sources include primary, secondary and tertiary data sources. Data collection techniques in the form of literature studies. The data analysis technique used is descriptive qualitative.Results of the Research: The results showed that there were violations against the civilian population in the Nagorno-Karabakh conflict area by the State of Armenia and Azerbaijan, in the form of killing, raping, holding hostages, and discrimination.